2013
DOI: 10.1038/emi.2013.54
|View full text |Cite
|
Sign up to set email alerts
|

Rapidly produced SAM® vaccine against H7N9 influenza is immunogenic in mice

Abstract: The timing of vaccine availability is essential for an effective response to pandemic influenza. In 2009, vaccine became available after the disease peak, and this has motivated the development of next generation vaccine technologies for more rapid responses. The SAM® vaccine platform, now in pre-clinical development, is based on a synthetic, self-amplifying mRNA, delivered by a synthetic lipid nanoparticle (LNP). When used to express seasonal influenza hemagglutinin (HA), a SAM vaccine elicited potent immune … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
181
0
6

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 211 publications
(188 citation statements)
references
References 29 publications
1
181
0
6
Order By: Relevance
“…However, to our knowledge, only two nonviral in vivo delivery methods have been reported. These methods include a cationic nanoemulsion, comprising cationic lipid 1,2-Dioleoyl-3-trimethylammonium propane emulsified with the constituents of the MF59 adjuvant (26,28), and a 1,2-dilinoleyloxy-3-dimethylaminopropane (DLinDMA)-centric lipid nanoparticle (27,29), both of which are five-component systems. Although these methods have been used as a synthetic delivery method for a chimeric SIN/VEEV replicon vaccine in vivo, they have yet to show protection against lethal pathogen challenges (27-29).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, to our knowledge, only two nonviral in vivo delivery methods have been reported. These methods include a cationic nanoemulsion, comprising cationic lipid 1,2-Dioleoyl-3-trimethylammonium propane emulsified with the constituents of the MF59 adjuvant (26,28), and a 1,2-dilinoleyloxy-3-dimethylaminopropane (DLinDMA)-centric lipid nanoparticle (27,29), both of which are five-component systems. Although these methods have been used as a synthetic delivery method for a chimeric SIN/VEEV replicon vaccine in vivo, they have yet to show protection against lethal pathogen challenges (27-29).…”
Section: Discussionmentioning
confidence: 99%
“…Nonretroviral RNA vaccines are attractive due to their inherent transience and absence of recombination or integration into the patient's genome. However, RNA-based vaccines require intracellular delivery methods to function (24)(25)(26)(27)(28)(29).…”
mentioning
confidence: 99%
“…We recently demonstrated that self-amplifying mRNA vaccines encoding influenza HA, and formulated with lipid nanoparticles were immunogenic in mice (43). In the present study, we demonstrate that SAM(HA) vaccine formulated with a novel cationic nanoemulsion (CNE) (50,52) elicits broad and efficacious immune responses to influenza in mice and ferret models.…”
mentioning
confidence: 66%
“…Recently, enhanced delivery technologies, such as electroporation (37,38), and improved immunogenicity by triggering innate immune cells have increased the efficacy of DNA vaccines in clinical trials (39). Vaccines based on mRNA or RNA replicons are immunogenic in a variety of animal models, including nonhuman primates (40)(41)(42)(43)(44). RNA replicons are derived from the genomes of RNA viruses, such as alphaviruses, and have been engineered by eliminating the genes encoding the structural proteins and replacing them with genes of interest.…”
mentioning
confidence: 99%
“…During the same time frame, the synthetic HA gene from the H7N9 strain of influenza virus was used in the self-amplifying mRNA system, which is an entirely synthetic RNA vaccine that is delivered by lipid nanoparticles [25,26]. After merely one month, the vaccine was ready for immunization and analysis in animal models of infection [27]. These new technologies have made it possible for an incredibly rapid response to emerging infectious diseases and global threats such Ebola.…”
Section: (E) From Genomes To Reverse Vaccinologymentioning
confidence: 99%